Students' Perception of The Competence of Guidance and Counseling Teachers at Madrasah Aliyah Almaarif Singosari - Rahmatillah, Aushaf Iklil; Simarmata, Devi Yustina B.R.; Afifah, Rohmatul; Simon, Irene Maya; Muyassaroh, Zahrotul; Apriani, Rizka (Proceedings Series of Educational Studies, 2024)
This study examines students' perception of the competence of BK teachers at Madrasah Aliyah Almaarif Singosari. This research was conducted based on the assumption from students that the services in the classroom are not fun and monotonous, even some students are lazy to listen and understand the meaning of the material conveyed if it is not in the form of a game method. In addition, some students are also worried that if they confide in the BK teacher, it will leak everywhere. This research is a field research using a qualitative approach and a phenomenological study research method. The subjects of this study are class XI students and students who have and have never counseled with BK teachers. Data collection in this study uses interviews and observations and is analyzed using Miles and Huberman’s qualitative descriptive analysis. Data analysis was carried out using Miles and Huberman techniques, including data reduction, data presentation, and conclusions drawn. This research procedure consists of 3 stages: 1) Preparation stage, 2) Implementation stage, 3) Final stage. The results of the study show that students' perception of the competence of Guidance and Counseling teachers is quite good, especially in social and personality competencies, and requires further evaluation in pedagogic and professional competence. Keywords: Perception; Competence; Students